Water Use Trend At Universiti Teknologi Malaysia: Application Of Arima Model - Katimon, Ayob; Demun, Amat Sairin (Penerbit UTM Press, 2004)

(untitled)
The Paper Describes The Application Of Autoregressive Integrated Moving Average (ARIMA) Model To Represent Water Use Behaviour At Universiti Teknologi Malaysia (UTM) Campus. Using Autocorrelation Function (ACF), Partial Autocorrelation Function (PACF), And Akaike’s Information Criterion (AIC), Monthly Campus Water Use Series Can Be Best Presented Using ARIMA (2,0,0) Model. The Estimated Parameter Of The Model ö1 And ö2 Are 0.2747 And 0.4194 Respectively. This Implies That Water Consumption In UTM Campus At The Present Month Is Not Necessarily Influenced By Water Consumption Of Immediate Previous Month. Analysis Shows That ARIMA (2,0,0) Model Provides A Reasonable Forecasting Tool For Campus Water Use.